Mechanical properties, wear and corrosion of boronized N80 tube steel - Xu, D.S.; Xu, X.; Su, Z.G.; An, J.; Lu, Y. (Фізико-хімічна механіка матеріалів, 2012)
The effect of boronizing on mechanical properties, wear and corrosion of boronized N80 tube steel is studied. A dual-phase boride layer consisting of FeB and F₂B phases was formed on the surface of steel substrate in a hardness range of 1220 to1340 HV. A set-up to use less boriding agent and accelerate the pipe’s cooling process was designed. In order to meet the tensile properties of N80 steel required by API SPEC 5L, four cooling methods were employed. The fan-cooling with a graphite bar inside the boriding agent resulted in the highest mechanical properties, in accordance with the mechanical properties of API SPEC 5L. The boronized N80 steel showed a high wear resistance under dry sliding condition and excellent corrosion resistance in as-received oilfield water from Jilin oil field, Northeast China. Изучено влияние борирования на механические свойства, изнашивание и коррозию трубной стали N80. На поверхности стальной подкладки сформирован двухфазный боридный слой на основе FeB и F₂B с твердостью 1220...1340 HV. Разработаны способы для уменьшения количества компонента для борирования и ускорения охлаждения. Для обеспечения высоких механических характеристик при растяжении согласно спецификации API SPEC 5L использованы четыре метода охлаждения. Вентиляторное охлаждение с графитовым бруском внутри борированного реагента обусловило наиболее высокие механические характеристики. Борированная сталь выявила высокие износостойкость в условиях сухого трения и коррозийную прочность в воде нефтяного промысла в Китае в провинции Джулин. Вивчено вплив борування на механічні властивості, зношування та корозію трубної сталі N80. На поверхні сталевої підкладки сформовано двофазний боридний шар на основі FeB і F₂B з твердістю 1220...1340 HV. Розроблено способи для зменшення кількості компонента для борування та пришвидшення охолодження. Для забезпечення високих механічних характеристик за розтягу згідно зі специфікацією API SPEC 5L використано чотири методи охолодження. Вентиляторне охолодження з графітовим бруском всередині борувального реагента призвело до найвищих механічних характеристик. Борована сталь виявила високі зносотривкість за сухого тертя та корозійну міцність у воді з нафтового родовища в Китаї у провінції Джулін.